Novel injectable gellan gum hydrogel composites incorporating Zn- and Sr-enriched bioactive glass microparticles: High-resolution X-ray microcomputed tomography, antibacterial and in vitro testing - Douglas, Timothy E. L.; Weinhardt, Venera (Journal of tissue engineering and regenerative medicine, 2018)
Mineralization of hydrogel biomaterials is desirable to improve their suitability as materials for bone regeneration. In this study, gellan gum (GG) hydrogels were formed by simple mixing of GG solution with bioactive glass microparticles of 45S5 composition, leading to hydrogel formation by ion release from the amorphous bioactive glass microparticles. This resulted in novel injectable, self-gelling composites of GG hydrogels containing 20% bioactive glass. Gelation occurred within 20 min. Composites containing the standard 45S5 bioactive glass preparation were markedly less stiff. X-ray microcomputed tomography proved to be a highly sensitive technique capable of detecting microparticles of diameter approximately 8 μm, that is, individual microparticles, and accurately visualizing the size distribution of bioactive glass microparticles and their aggregates, and their distribution in GG hydrogels. The widely used melt-derived 45S5 preparation served as a standard and was compared with a calcium-rich, sol-gel derived preparation (A2), as well as A2 enriched with zinc (A2Zn5) and strontium (A2Sr5). A2, A2Zn, and A2Sr bioactive glass particles were more homogeneously dispersed in GG hydrogels than 45S5. Composites containing all four bioactive glass preparations exhibited antibacterial activity against methicillin-resistant Staphylococcus aureus. Composites containing A2Zn5 and A2Sr5 bioactive glasses supported the adhesion and growth of osteoblast-like cells and were considerably more cytocompatible than 45S5. All composites underwent mineralization with calcium-deficient hydroxyapatite upon incubation in simulated body fluid. The extent of mineralization appeared to be greatest for composites containing A2Zn5 and 45S5. The results underline the importance of the choice of bioactive glass when preparing injectable, self-gelling composites.
Gesehen am 13.06.2019